Understanding Consumers’ Attitudes Toward Fruits and Vegetable Attributes: A Multi-Method Approach - Thomas, Terrence; Gunden, Cihat; Miran, Bulent (Journal of Nutritional Therapeutics, 2015)
Background: Results from previous work indicated that when consumers make purchasing decisions, they pay more attention to freshness, taste and hygiene attributes of fruits and vegetables than price and nutritional value, when these attributes are considered individually. Methods: To shed light on the underlying factors that shape the pattern of reported preferences, researchers used five doubly censored Tobit models to analyze data generated from a fuzzy pairwise comparison model (FPC) to explain the pattern of reported preferences. In the model, nutritive value, hygiene, taste, price and freshness were separately regressed on a number of demographic and personal characteristics variables. For this study, a random sample was drawn proportionate to population size by county in Georgia, North Carolina and South Carolina. Data were collected from 412 respondents. Results: Higher levels of education and income did not affect how consumers rate the nutritional value of fruits and vegetables. This relative lack of difference among consumers as classified in the model, along with results that showed consumers giving a higher preference rating to hygiene, taste and price offer support for the notion that the nutritional value attribute plays a subsidiary role in consumers purchasing decisions. Conclusion: The multi-method approach used in this study provides information on the demographic characteristics of consumers that influence attitudes and behaviors toward fruit and vegetable attributes. Nutrition educators and marketers will be able to use this knowledge about consumers’ attitudes and behaviors to customize programs that more accurately address consumers’ preferences.